AN ANALYSIS OF EMPLOYEE SERVICE PERFORMANCE OF PT FUJI SEAT INDONESIA - Mega Putra Atmana Negara; Uus MD Fadli; Enjang Suherman (Jurnal Ekonomi, 2023)
Employee service performance is one of the important factors to achieve company goals. Good service performance is needed so that the entire service process carried out by employees supports the achievement of the company's vision. Employees must be truly competent in their fields, able to serve optimally and be able to serve the needs of internal and external customers well. The purpose of this study is to explain the service performance of employees, both to superiors, subordinates, colleagues, and external customers at PT Fuji Seat Indonesia, by existing procedures in the company. It is hoped that the results of this study can evaluate the service performance of employees so far and can improve service performance in the future optimally. The research method uses a quantitative descriptive approach, the sample is 101 employees of PT Fuji Seat Indonesia, and primary data is collected through questionnaires. Furthermore, the data were analyzed using factor analysis. The results of the study indicate that the factors that affect the service performance of employees at PT Fuji Seat Indonesia consist of interpersonal impact factors with members of this factor, namely feelings of pleasure, leadership motivation, leadership appreciation, and completing work without waiting for orders; timeliness factor with the members of this factor is punctuality, time discipline level, service process, and load fulfillment; and the need for supervision factor with members of this factor, namely target achievement and leadership support